Inverse logistics in the manufacturing sector and its impact on the environment - Salas Valdivia, Elard Thamar (2020)
The aim of this research was to highlight the importance of Reverse Logistics management as a mechanism to take advantage of disposable resources to give them an opportunity of economic value. The research was based on the existence of an increasing in the beneﬁt of Reverse Logistics in the relationship between the company and the environment. Environmental, cultural and social trends, and the scarcity of natural resources require Graphics Industry companies to optimize through Reverse Logistics, as a support not only in their operational performance, but even more, the degree of reasonable competitiveness in their resources and capabilities. The methodology used consisted of the documentary review in relation to the Reverse Logistics issue that exists in the literature, in the period between 1990 and 2017. As a result, it could be highlighted that the organization's strategy should focus on the main competitiveness it has and that it could maximize the value of the organization. In conclusion, it was possible to emphasize the economic advantages that are widely considerable for companies and their implications on the issue of environmentally sustainable economic activities.